Power over Fiber for Internet of Things Application - Mohammed A.I.A.; Ker P.J.; Lee H.J.; Muhamad M.; Zuhdi A.W.M.; Gamel M.M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cables; Copper; Efficiency; Photonics; Distribution systems; Emergency conditions; Internet of thing (IoTs); Main parameters; Maximum Efficiency; Optical-to-electrical conversion; Overall efficiency; Power over fiber; Internet of things